"Double whammy" to the kidneys: an unusual etiology of acute kidney disease - Varadharajan Jayaprakash; Muthukaruppaiah Suganya; Dhanasekaran Karthick; Anila Abraham Kurien; Raghavan Padmanabhan (Society of Diabetic Nephropathy Prevention, 2023)
Severe rhabdomyolysis could lead to myoglobinuria and acute kidney injury (AKI). Acute interstitial nephritis (AIN) is commonly caused by drugs. AIN per se can cause 'severe' AKI. Renal recovery is delayed when several factors are involved in the pathogenesis of AKI. Survivors of AKI require long-term follow-up. Here, we report a case where both severe rhabdomyolysis and drug-induced AIN contributed to 'severe' dialysis-requiring AKI. Renal biopsy was diagnostic and showed characteristic features. Steroid therapy for AIN resulted in partial recovery.